2019
DOI: 10.1177/1049731519832105
|View full text |Cite
|
Sign up to set email alerts
|

Elements of a College Support Program That Matter: A Case Study

Abstract: Purpose: This study focuses on a campus support program that serves former child welfare and homeless youth. This study aims to identify the program elements that help students transition into and succeed in college. Method: This study uses a mixed-method approach. Quantitative data included administrative and survey data of 50 students. Bivariate and multivariate analyses were used to examine the effects of early engagement on students’ grade point averages (GPAs). Qualitative data were collected from intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…One study found that early engagement in college support programs has potential for enhancing success for students experiencing homelessness at the university level (Huang et al, 2019). Thus, school counselors can identify universities with strong programs and partner with them to get students enrolled immediately upon their entrance to college.…”
Section: Discussionmentioning
confidence: 99%
“…One study found that early engagement in college support programs has potential for enhancing success for students experiencing homelessness at the university level (Huang et al, 2019). Thus, school counselors can identify universities with strong programs and partner with them to get students enrolled immediately upon their entrance to college.…”
Section: Discussionmentioning
confidence: 99%